Consumer Loyalty: Brand Perception, Trust, Product Quality, and the Mediating Role of Customer Satisfaction: Setia Konsumen: Persepsi Merek, Kepercayaan, Kualitas Produk, dan Pengaruh Mediasi Kepuasan Pelanggan. - Muhammad Eko Rizky; Misti Hariasih Hariasih (Academia Open, 2024)
This study investigates the influence of brand image, brand trust, and product quality on consumer loyalty towards Converse footwear, utilizing customer satisfaction as an intervening variable. Conducted among Converse shoe consumers in Sidoarjo, the research employs a quantitative approach with accidental sampling. Data is collected through questionnaires distributed to consumers. Path analysis using SPSS reveals that brand image, brand trust, and product quality significantly affect consumer loyalty through customer satisfaction as an intervening factor. These findings provide valuable insights for brand management and marketing strategies in the global footwear industry. Highlights: The study focuses on consumer loyalty in the context of Converse footwear. It highlights the role of customer satisfaction as an intervening variable. Findings provide insights for global brand management and marketing strategies. Keywords: Brand Image, Brand Trust, Product Quality, Consumer Loyalty, Customer Satisfaction